Upaya Meningkatkan Kemajuan UMKM Kemplang Asrania di Pemulutan Ilir Melalui Peningkatan Kualitas SDM - Helmi, Sulaiman; Rosa, Alkirma; Ariana, Sunda (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy but still require development, especially in improving the quality of human resources. Focusing on improving human resources in MSMEs, such as those of Ms. Asrania's Kemplang Business in Pemulutan Ilir, is crucial to improving the competitiveness and sustainability of MSMEs. The study aimed to investigate ways to enhance the advancement of Kemplang MSMEs by enhancing the caliber of their workforce. This endeavor seeks to offer deeper insights and a significant contribution to the field of science, particularly in the micro, small, and medium-sized economies, laying a foundation for future research in this domain. The MSME development program through improving human resources in Pemulutan Ilir Village lasted for two months and targeted the community around the village.